Analisis Psikologis Tokoh Sarah dalam Cerpen Menu Musim Semi Karya O. Henry - Bintang Pastika Alwie; Talita Dian Ciptaningrum; Eva Dwi Kurniawan (J-CEKI : Jurnal Cendekia Ilmiah, 2023)
This research aims to examine the personality of the character Sarah in the short story Menu Musim Spring by O. Henry from the perspective of Literary Psychology. The research used is qualitative research. The researcher tries to analyze the personality of the character Sarah in the short story Menu Musim Spring. The method used uses a literary psychology approach with Sigmund Freud's theory. The description of this character is Sarah, a girl who experiences feelings of sadness and despair amidst her boring job as a typist. Despite his flat life, he finds solace in spring with a farmer named Walter Franklin. However, at one point her feelings were shattered when a letter from Walter did not reach her hands. She was enveloped in feelings of loss and disappointment, making her mood change until one day she met Walter unexpectedly. Warter met Sarah by coming to her house and showing that their love was still strong.